A<small.letters>po</small.letters>E Polymorphism is Associated With C-Reactive Protein in Low-HDL Family Members and in Normolipidemic Subjects (Mediators of Inflammation)
The study was aimed to compare inflammatory parameters between carriers of apoE4 isoforms (apoE4/3, apoE4/2, and apoE4/4 phenotypes) and those of carrying apoE3 isoform without apoE4 isoform (apoE3/3 phenotypes and apoE2/3 phenotypes). The concentrations of serum hsCRP, sVCAM-1, sICAM-1, and sE-selectin were measured in 211 subjects from Finnish low-HDL families and in 157 normolipidemic subjects. The subjects with apoE4 isoform had lower concentrations of serum hsCRP both in low-HDL family members ( p<0.05 ) and in normolipidemic subjects ( p<0.01 ). The differences in serum CRP values remained significant after adjustment for age, BMI, smoking status, hypertension, gender, lipoprotein variables, and family number. We conclude that apoE phenotype has a strong influence on serum CRP values.